The Dandelion Dilemma Revisited for Oligoprogression: Treat the Whole Lawn or Weed Selectively?. Issue 12 (December 2019) - Patel, P.H.; Palma, D.; McDonald, F.; Tree, A.C.
Abstract: Oligoprogressive disease is a relatively new clinical concept describing progression at only a few sites of metastasis in patients with otherwise controlled widespread disease. In the era of well-tolerated targeted treatments, resistance inevitably occurs and overcoming this is a challenge. Local ablative therapy for oligoprogressive disease may allow the continuation of systemic treatments by overcoming the few sub-clones that have developed resistance. Stereotactic body radiotherapy is now frequently used in treating oligometastatic disease using ablative doses with minimally invasive techniques and acceptable toxicity. We discuss the current retrospective clinical evidence base supporting the use of local ablative therapy for oligoprogression in metastatic patients on targeted treatments within multiple tumour sites. As there is currently a lack of published prospective data available, the best management for these patients remains unclear. We discuss current trials in recruitment and the potential advancements in treating this group of patients with stereotactic radiotherapy.